Food composition of Indian Eagle Owl Bubo bengalensis Franklin (Aves: Strigiformes: Strigidae) from Tiruchirappalli District, Tamil Nadu, India - Tamilselvan Siva; Periyasamy Neelanarayanan; Vaidyula Vasudeva Rao (Journal of Threatened Taxa, 2019)
The diet of the Indian Eagle Owl was studied from April to September 2017 in Tiruchirapalli District, Tamil Nadu, India.  Analysis of 1082 regurgitated pellets yielded 2077 prey items; the mean prey items/ pellet was 1.91.  The diet constituted 65.1% of rodent prey and the remaining 34.83% of other groups of both vertebrate and invertebrate animals.  The mean percentage of prey composition was 31.15% Millardia meltada Soft-furred Field Rat, 12.95% Bandicota bengalensis Lesser Bandicoot Rat, 10.25% Mus booduga Indian Field Mouse, and 10.24% of other rodent species.  Of the 34.83% of non-rodent prey, the owls ingested insects (Rhinoceros beetles, 9.58%), Arachnida (Solifugae or Sun spider, Galeodes sp., 9.58%), reptiles (Calotes sp., 3.7%), amphibians (3.56%), shrews (Suncus murinus, 2.84%), and others (5.57%).  The Indian Eagle Owls consumed more than one prey per day and chiefly foraged in agricultural crop fields and consumed both small mammals and insects of agricultural importance under crop ecosystems.